Separation of Flavonoids from Crude Extract of Gynura divaricata by Macroporous Resin - Jie, Min; Wan, Chunpeng; Yu, Yanying; Cao, Shuwen (Asian Journal of Chemistry, 2011)
The flavonoids in Gynura divaricata has obvious effect of glucose-lowering and antiatheroscloresis. In this paper, an efficient separation process of the flavonoids from Gynura divaricata crude extracts has been developed. During the five kinds of macroporous resins tested preliminarily, HPD-100 offers the best adsorption capacity, so the dynamic adsorption and desorption experiments have been carried out on it to optimize the separation process of the flavonoids from Gynura divaricata crude extracts further. After treatment with HPD-100 resin under the optimal conditions, the flavonoids content was increased more than 6-fold from 7 to 43 %, with a recovery yield of 85 % and the content of kaempferol-3-O-glucoside enhanced 7-fold. It is concluded that the results in this study may provide a potential approach for the large-scale flavonoids production from Gynura divaricata extracts for its medicinal use.